2008
DOI: 10.1080/01421590701754144
|View full text |Cite
|
Sign up to set email alerts
|

Comparing academic performance of medical students in distributed learning sites: the McMaster experience

Abstract: This study has shown that academic performance among students was at least comparable across all learning sites. To our knowledge, this is the first such study to be published within a Canadian context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…In those studies that used objective measures such as exam scores, USMLE scores, or performance on clinical skills testing, students with rural experiences generally did equally as well or better than their counterparts. Bianchi and colleagues 14 found that students with rural experiences had higher clinical exam scores, whereas Power and colleagues 15 Impact of Rural Care Education found that rural students did equally well on OSCE stations using primary care problems but slightly worse on stations assessing specific content taught in traditional clerkship curricula. Although a 1983 study 33 showed slightly lower grades and NBME scores for rural program students, more recent studies showed either no difference on test scores 8,17 or found lower USMLE Step 1 scores for rural students but higher USMLE Step 2 scores.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies that used objective measures such as exam scores, USMLE scores, or performance on clinical skills testing, students with rural experiences generally did equally as well or better than their counterparts. Bianchi and colleagues 14 found that students with rural experiences had higher clinical exam scores, whereas Power and colleagues 15 Impact of Rural Care Education found that rural students did equally well on OSCE stations using primary care problems but slightly worse on stations assessing specific content taught in traditional clerkship curricula. Although a 1983 study 33 showed slightly lower grades and NBME scores for rural program students, more recent studies showed either no difference on test scores 8,17 or found lower USMLE Step 1 scores for rural students but higher USMLE Step 2 scores.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while there is evidence demonstrating equivalent placement assessment marks across geographical settings for medical students the same has not been explored for physiotherapy student placements. [12][13][14][15][16][17][18][19][20] The aims of this study were to describe the geographical distribution of physiotherapy clinical placements, and to investigate the relationship between geographical setting and clinical placement marks in physiotherapy students.…”
Section: Introductionmentioning
confidence: 99%
“…While Australian and Canadian studies demonstrate that assessment results of students studying in dispersed rural communities are similar to those studying in traditional urban settings (Worley et al 2004;Bianchi et al 2008), some schools will face problems managing issues relating to consistency of experience, supervision and assessment. At JCU, analysis of results by site has not shown significant differences in student performance by clinical school.…”
Section: The Jcu Contextmentioning
confidence: 99%